Potential of Pinus glabra wood for pulp production - Vivian, Magnos Alan; Modes, Karina Soares; Caetano, Ana Paula (Instituto de Ecología, A.C., 2020)
For more than a century the species of Pinus have been present in Brazil, especially Pinus taeda, with applications in several sectors. However, for Pinus glabra, object of this study, there is not much information about the technological potential of its wood. Thus, the objective of the study is to make inferences about the quality of the P. glabra wood for pulp production, comparing it to P. taeda, the main species used to produce long fiber pulp in Brazil. For that, four trees were cut, from which samples were removed for the physical, chemical, and anatomical characterization of the wood. In relation to the basic density, it was observed the mean and weighted values of 0.421 g/cm-3 and 0.424 g/cm-3, respectively, which classifies it as low density. In anatomical characterization, mean values of length of 3.14 mm, width of 27.18 μm, lumen diameter of 15.39 μm and wall thickness of 5.89 μm of the tracheids were obtained, which resulted in 44.72%, 55.28%, 0.90 and 120.72 for the parameters of wall fraction, flexibility coefficient, Runkel index and felting index, respectively. For the chemical composition, low ash contents (0.25%) and extractives (1.91%) were observed, and intermediate lignin (29.93%) and holocellulose (67.91%) contents were observed. In this way, P. glabra wood presents potential for the pulp production, which must be proven through pulping tests.